Affinity Networks as a Tool for Assessing Writing Processes: A Novel Method Utilizing Pause-Based Visibility Graphs - Oliveira, Davi Alves; Rodrigues, Erica dos Santos; Pereira, Hernane Borges de Barros (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM), 2023)
This study proposes utilizing affinity networks to characterize writing profiles by examining pausing behavior during writing tasks. Data from 34 participants was collected using Inputlog. Pauses were used to create visibility graphs, and the resulting graph metrics were used to build an affinity network. The network was then analyzed to group writers based on their pausing behavior. Results indicate that this method can be used to identify different writing profiles of writers with distinct proficiency in text production. Future research should investigate if changes in pausing behavior can improved writing proficiency.